La Academia (Greco)latina Matritense (1755-1849). Segunda parte: actividad filológica y documentos (Minerva, 2019)
We continue our historical approach to the Academia Grecolatina Matritense with the study of its philological activities, scholar editions, translations, and a complete bibliography about the institution.
Keywords: Academia Grecolatina Matritense; classical studies; Spain; XVIII-XIX centuries